Data Analysis self-efficacy hearing loss - Rosyad, Yafi Sabila; Aljaberi, Musheer Abdulwahid; Natarajan , Satheesh Babu (Journal of health research and technology, 2025)
Introduction: Hearing loss affects millions worldwide, impacting communication and well-being. Self-efficacy, or confidence in overcoming challenges, is crucial for adaptation. This study examines trends in self-efficacy research for individuals with hearing loss, focusing on academic contributions and interventions. Methods: A descriptive analysis of Scopus database articles was conducted, examining authorship, institutional contributions, subject areas, publication trends, and geographic research distribution. Results: The analysis reveals increasing academic interest in self-efficacy and hearing loss, with contributions spanning multiple disciplines. Key topics include communication strategies, social participation, and psychological adaptation. Developed countries contribute the most research, while developing regions show gaps. The study also identifies leading authors, institutions, and frequently cited sources in this field. Conclusion: This study provides a foundation for further research and practical applications to enhance self-efficacy in individuals with hearing loss. Addressing research gaps and promoting inclusive policies can improve social integration and overall quality of life.